Creating hemodynamic atlases of cardiac 4D flow MRI. Issue 5 (13th March 2017) - Cibis, Merih; Bustamante, Mariana; Eriksson, Jonatan; Carlhäll, Carl‐Johan; Ebbers, Tino
Abstract : Purpose: Hemodynamic atlases can add to the pathophysiological understanding of cardiac diseases. This study proposes a method to create hemodynamic atlases using 4D Flow magnetic resonance imaging (MRI). The method is demonstrated for kinetic energy (KE) and helicity density (Hd ). Materials and Methods: Thirteen healthy subjects underwent 4D Flow MRI at 3T. Phase‐contrast magnetic resonance cardioangiographies (PC‐MRCAs) and an average heart were created and segmented. The PC‐MRCAs, KE, and Hd were nonrigidly registered to the average heart to create atlases. The method was compared with 1) rigid, 2) affine registration of the PC‐MRCAs, and 3) affine registration of segmentations. The peak and mean KE and Hd before and after registration were calculated to evaluate interpolation error due to nonrigid registration. Results: The segmentations deformed using nonrigid registration overlapped (median: 92.3%) more than rigid (23.1%, P < 0.001), and affine registration of PC‐MRCAs (38.5%, P < 0.001) and affine registration of segmentations (61.5%, P < 0.001). The peak KE was 4.9 mJ using the proposed method and affine registration of segmentations ( P  = 0.91), 3.5 mJ using rigid registration ( P < 0.001), and 4.2 mJ using affine registration of the PC‐MRCAs ( P < 0.001). The mean KE was 1.1 mJ using the proposed method, 0.8 mJ using rigid registration ( P < 0.001), 0.9 mJ using affine registration of the PC‐MRCAs ( P < 0.001), and 1.0 mJ using affine registration of segmentations ( P  = 0.028). The interpolation error was 5.2 ± 2.6% at mid‐systole, 2.8 ± 3.8% at early diastole for peak KE; 9.6 ± 9.3% at mid‐systole, 4.0 ± 4.6% at early diastole, and 4.9 ± 4.6% at late diastole for peak Hd . The mean KE and Hd were not affected by interpolation. Conclusion: Hemodynamic atlases can be obtained with minimal user interaction using nonrigid registration of 4D Flow MRI. Level of Evidence: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2017;46:1389–1399.